2023
DOI: 10.3389/fneur.2023.1154753
|View full text |Cite
|
Sign up to set email alerts
|

Mitoepigenetics and gliomas: epigenetic alterations to mitochondrial DNA and nuclear DNA alter mtDNA expression and contribute to glioma pathogenicity

Abstract: Epigenetic mechanisms allow cells to fine-tune gene expression in response to environmental stimuli. For decades, it has been known that mitochondria have genetic material. Still, only recently have studies shown that epigenetic factors regulate mitochondrial DNA (mtDNA) gene expression. Mitochondria regulate cellular proliferation, apoptosis, and energy metabolism, all critical areas of dysfunction in gliomas. Methylation of mtDNA, alterations in mtDNA packaging via mitochondrial transcription factor A (TFAM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 90 publications
0
2
0
Order By: Relevance
“…DNA methylation and CNV play crucial roles in the regulation of epigenetics. 37 , 38 Studies have shown that epigenetic gene reprogramming could be a fundamental driving force in gliomas. 39 This suggests that the abnormal elevation of CTHRC1 may be regulated by epigenetic mechanisms, thereby enhancing the invasive ability of gliomas.…”
Section: Discussionmentioning
confidence: 99%
“…DNA methylation and CNV play crucial roles in the regulation of epigenetics. 37 , 38 Studies have shown that epigenetic gene reprogramming could be a fundamental driving force in gliomas. 39 This suggests that the abnormal elevation of CTHRC1 may be regulated by epigenetic mechanisms, thereby enhancing the invasive ability of gliomas.…”
Section: Discussionmentioning
confidence: 99%
“…Glioblastoma (GBM) is the most aggressive primary brain tumour in adults, that accounts for more than 60% of all brain tumours in adults [ 1 , 2 ]. Thought to originate from glial cells and neural stem cells (NSCs), GBM is classified as a WHO grade 4 glioma, responsible for over 15,000 deaths annually in the US alone [ 3 5 ]. A recent study in Norway determined median overall survival to be ~ 12 months, with 2- and 5-year median survivals of ~ 21% and 7%, respectively [ 6 ].…”
Section: Overview Of Current Glioblastoma Treatmentsmentioning
confidence: 99%